THE IMPORTANCE OF IMPLEMENTING FINANCIAL MANAGEMENT, CONTROL, AND IT IN PUBLIC SECTOR OPERATIONS IN THE REPUBLIC OF SERBIA - Popović, Slobodan; Arnautović, Ivan; Sredojević, Dejan; Brakus, Aleksandra (The European Journal of Applied Economics, 2025)
The goal of the work was to find out the trust of top managers of commercial banks, the management of the management bodies of local self-government units and top managers of public companies regarding the implementation of financial management and control, which is achieved by the application of IT systems as a management decision support system. We discovered that there are big differences in entities that did not implement financial management and control in regular business compared to those entities that did. In addition, in the following period, the factors given in the research should be taken into account, such as: completeness of beliefs, economy in work, business efficiency, effective business, contribution to the development of a public company and the overall score, as well as the fact that there is a significant deviation when observing those entities that do not apply and those that apply the mentioned control in business. In the end, the work indicates that it is possible to forecast future business, based on all three levels of management, primarily the public sector, as well as that it is necessary to consider innovative efforts such as the application of IT support systems.
Keywords: financial management and control, IT system, public company.